2017
DOI: 10.1002/dmrr.2892
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end‐products (AGEs) and associations with cardio‐metabolic, lifestyle, and dietary factors in a general population: the NQplus study

Abstract: This cross-sectional study in a general population showed that age and coffee intake were associated with skin AF in both males and females. We observed a gender disparity for some of the associations with skin AF, which need to be confirmed by further research. More detailed research is needed to assess the association between skin AF and diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
(124 reference statements)
4
15
2
Order By: Relevance
“…SAF increases with age, the strongest risk factor for cardiovascular events in T1D [ 8 ]. SAF has recently been related to the components of the metabolic syndrome [ 34 ], especially low HDL-cholesterol and arterial hypertension [ 35 ], that increasingly mediate the effect of glucose control on cardiovascular risk in aging T1D [ 5 ]. The progression of SAF in our patients with T1D highly depends on their glomerular filtration rates [ 15 ], as expected because renal insufficiency reduces the clearance of AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…SAF increases with age, the strongest risk factor for cardiovascular events in T1D [ 8 ]. SAF has recently been related to the components of the metabolic syndrome [ 34 ], especially low HDL-cholesterol and arterial hypertension [ 35 ], that increasingly mediate the effect of glucose control on cardiovascular risk in aging T1D [ 5 ]. The progression of SAF in our patients with T1D highly depends on their glomerular filtration rates [ 15 ], as expected because renal insufficiency reduces the clearance of AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…We found positive correlations between SAF and age, both in psoriatic patients and healthy controls. Correlations between SAF and age were previously reported [ 31 , 32 ]. Although we did not find any significant difference in SAF between the whole group of patients with psoriasis and controls, we showed that individuals suffering from psoriasis, with elevated CRP levels and increased ESR, had significantly increased SAF as compared to controls.…”
Section: Discussionmentioning
confidence: 82%
“…The interaction between AGE-RAGE, or RAGE-other ligands, on inflammatory cells stabilizes the receptor in the active state and amplifies inflammation by favoring the release of cytokines and chemokines, the production of reactive oxygen species and the activation of metalloproteases. Inflammation in turn is associated with induction of more AGEs, thus spreading the inflammatory response through this vicious circle formation [ 21 ].…”
Section: Advanced Glycation End Products (Ages)mentioning
confidence: 99%
“…Excessive AGEs accumulation in tissues has been documented in different disorders particularly in metabolic diseases such as diabetes and obesity and AGEs may have a relevant role in the tissue changes and clinical complications associated with these diseases [ 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Advanced Glycation End Products (Ages)mentioning
confidence: 99%
See 1 more Smart Citation